OPTIMALISASI LUBE OIL COOLER TIPE FIN & TUBE HEAT EXCHANGER PADA PROSES PELUMASAOPTIMALISASI LUBE OIL COOLER TIPE FIN & TUBE HEAT EXCHANGER PADA PROSES PELUMASAN MENGGUNAKAN METODE NTU (NUMBER TRANSFER OF UNIT)N MENGGUNAKAN METODE NTU (NUMBER TRANSFER OF UNIT) - Kurniawan, Kurniawan; Budihadi, Agus (Universitas Mercu Buana, 2023)
The lube oil cooler is one of the tools in the PLTGU lubrication system. The lube oil cooler functions to keep the lubricating oil temperature in the turbine at a normal temperature, namely ± 40 C. The temperature is maintained at normal temperatures to prevent damage to the bearings and overheating of the turbine. An overheated turbine will waste energy into heat energi. To maintain the temperature of the lube oil, a fin & tube type heat exchanger with crossflow flow was chosen. The design of the lube oil cooler begins by determining the initial design parameters for the cooling fluid and lubricating oil such as temperature, specific heat, mass flow rate, viscosity, density, and thermal conductivity. Furthermore, calculations are carried out using general equations and according to standards, simulation using Aspen Hysys V11 software and analyzing the design results. From calculaion we get dimentions of the lube oil cooler with an outside diameter 0,038 m, an inside diameter of 0,035 m, 18 BWG, a pipe length of 4,49 m, a number of 161 pipes, a number pipes per line 13 pieces with triangular shape and the number of pipes per row fins 2 pieces. The standard of lube oil cooler design is the value of pressure drop ≤ 0,68 bar, where the value of pressure drop on the duct side is 0,0075 bar and the tube side is 0.574 bar. For the simulation using aspen hysys V11, there is no error in the design as evidenced by the blue material flow and red energi flow. And the resulting effectiveness is 74.9 %. Keywords: Lube oil cooler, lubrication system, fin & tube, aspen hysys V11, Heat Exchanger